Isolation and Characterization of Sesquiterpenoids from Daphne acutiloba Rehd. - He1, Shun-Qin; Li1, Zhong; Ou1, Yang-Wen; Wang1, Lan; Yang1, Guang-Yu; Hu1, Qiu-Fen (Asian Journal of Chemistry, 2011)
A new sesquiterpenoid (daphnelnoid A), together with three known, were isolated from the leaf and steam of Daphne acutiloba Rehd. Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. The anti-HIV-1 activity of daphnelnoid A was also evaluated and it shows a moderate anti-HIV-1 activity with a therapeutic index above 45.2.